Is transparency spatially determined? An empirical test for Italian municipalities. Issue 58 (13th December 2020) - Galli, Emma; Rizzo, Ilde; Scaglioni, Carla
ABSTRACT: In this article, we aim to assess whether transparency is characterized by a spatial dimension. To this end, we use a new composite indicator (CTI) for a large sample of Italian municipalities and control for several factors (socio-economic, fiscal, and politico-institutional), which, according to the literature, affect transparency. Our results suggest that there is a statistically significant transparency clustering across the Italian municipalities which follows a dichotomic pattern, i.e. either very low or very high. Moreover, the empirical analysis shows that spatial dependence matters and 'transparency mimicking' takes place among neighbouring municipalities. This behaviour mainly occurs among small municipalities where citizens' political participation is likely to be greater and the single-ballot electoral system strengthens the incentives for government accountability.